Spatiotemporal analysis of setting per game complex and team rotation in junior volleyball - Michalopoulos, George; Sotiropoulos, Konstantinos; Drikos, Sotirios; Barzouka, Karolina; Angelonidis, Yannis (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. In volleyball, setting is a critical skill from a technical and tactical point of view, as it affects attack directly: the better the quality of the setter’s performance, the more excellent attack actions are carried out by men and women attackers. Aim of Study. This study aimed to assess the spatial and temporal characteristics of the setting choices made by junior male volleyball setters and their performance concerning the game complex per match rotation. Material and Methods. A three-member group of experienced coaches assessed the setting zones choices, the setting tempo, and the performance of junior male setters from 20 volleyball games of teams competing in the final phase of the 2016 Greek Junior Championship. A five-level ordinal scale was used to evaluate the setting. The test of independence for the categorical variables was carried out using the chi-square test (χ2). Following the overall independence test, the difference in proportions among all levels of variables was tested. Results. Results showed that zone 4 was the junior setters’ first choice irrespective of the game complex. More detailed, in Complex II, the most preferable setting zones were 4 and 6, while zone 3 was the primary selection in Complex I. The setting in the first tempo was the most favorite option in Complex I, although second slow tempo was the most frequently used setting option in Complex II. As for the quality of the setting, the dominant value for both complexes was quality level 2. Conclusions. In conclusion, the junior male setters directed the ball mainly to position 4 by using the slow 2nd tempo settings irrespective of the game rotation. Moreover, they showed a higher proportion of excellent setting actions and used fast settings (first tempo) more frequently in Complex I than in Complex II
Keywords: volleyball; juniors; high level; setter’s distribution; rotation; tempo of setting; performance analysis